확산된 피크의 양성자에서 선량 증강 현상에 대한 분석 - 황철환; Chulhwan Hwang; 김정훈; Junghoon Kim (한국방사선학회 논문지, 2019)
방사선 선량 증강은 물질과의 상호작용 단면적을 높여 국소 부위에 대한 선량을 증가시키는 방법으로 선에너지부여 및 상대적 생물학적 효과비 증가로 치료가능비 향상에 기여할 수 있다. 선량 증강에 대한 선행 연구는 X, γ선에 대한 보고가 주를 이루고 있으나, 본 연구에서는 MCNP6를 이용한 몬테칼로 시뮬레이션을 바탕으로 양성자 선원에 대해 선량 증강 현상을 분석하였다. 수학적 모델 방법에 따라 확산된 피크의 양성자 선원에 대한 에너지 분포와 상대적 강도를 산출하였으며, 금, 아이오딘, 가돌리늄의 선량 증강 물질에 대한 선량증강비와 깊이 변화에 따른 에너지 분포를 평가하였다. 금을 이용한 증강 현상에서 1.085-1.120배, 가돌리늄에서는 1.047-1.091배의 선량증강비를 나타내었다. 또한 깊이에 따른 흡수에너지 변화로 인해 실질 비정과 95% 선량 구간의 감소를 나타내었으며, 이는 선량 증강 현상과 더불어 종양조직에 불확실한 선량 전달로 이어질 수 있으므로 증강 물질의 질량 저지능으로부터 확산된 피크 구간의 적절한 보정이 필요할 것으로 사료된다. 본 연구에서 모의모사를 통한 선량 증강 현상의 분석은 실질적인 증강 효과 확인을 위한 체내·외 실험의 기초자료로써 활용될 것으로 기대한다. Radiation dose enhancement is a method of increasing the cross section of interaction, thus increasing the deposited dose. This can contribute to linear energy transfer, LET and relative biological effectiveness, RBE. Previous studies on dose enhancement have been mainly focused on X, γ-rays, but in this study, the dose enhancement was analyzed for proton using Monte Carlo simulation using MCNP6. Based on the mathematical modeling method, energy spectrum and relative intensity of spread out Bragg-peak were calculated, and evaluated dose enhancement factor and dose distribution of dose enhancement material, such as aurum and gadolinium. Dose enhancement factor of 1.085-1.120 folds in aurum, 1.047-1.091 folds in gadolinium was shown. In addition, it showed a decrease of 95% modulation range and practical range. This may lead to an uncertain dose in the tumor tissue as well as dose enhancement. Therefore, it is necessary to make appropriate corrections for spread out Bragg-peak and practical range from mass stopping power. It is expected that Monte Carlo simulation for dose enhancement will be used as basic data for in-vivo and in-vitro experiments.